The Effect of Xylooligosaccharide, Xylan, and Whole Wheat Bran on the Human Gut Bacteria - Chen, Miao; Liu, Shujun; Imam, Khandaker Md. Sharif Uddin; Sun, Lichao; Wang, Yulu; Gu, Tianyi; Wen, Boting; Xin, Fengjiao (Frontiers in Microbiology, 2020)
Wheat bran is a cereal rich in dietary fibers that has high levels of ferulic acid, which has prebiotic effects on intestinal microbiota and the host. Herein, we explored the effect of xylooligosaccharide, xylan, and whole wheat bran on the human gut bacteria and screened for potential ferulic acid esterase genes. Using in vitro fermentation, we analyzed the air pressure, pH value, and short-chain fatty acid levels. We also performed 16S rRNA gene and metagenomic sequencing. Venn diagram analysis revealed that 80% of the core operational taxonomic units (OTUs) were shared among the samples, and most of the xylooligosaccharide treatment core OTUs (319/333 OTUs) were shared with the other two treatments’ core OTUs. Significant difference analysis revealed that the relative abundance of Dorea, Bilophila, and Sulfurovum in the wheat bran treatment was higher than that in the xylan and xylooligosaccharide treatments. The Clusters of Orthologous Groups of proteins functional composition of all samples was similar to the microbiota composition of the control. Using metagenomic sequencing, we revealed seven genes containing the conserved residues, Gly-X-Ser-X-Gly, and the catalytic triad, Ser-His-Asp, which are thus potential ferulic acid esterase genes. All the results indicate that xylan and/or xylooligosaccharide, the main dietary fibers in wheat bran, play a major role in in vitro fermentation by the human gut microbiota.